Um estranho entre nós: A repercussão do diagnóstico de HIV/AIDS na trajetória de casais heterossexuais soroconcordantes - Daspett, Celina (2005)
The objective of this study is to know the repercussion of the positive sorology to the human imunodeficiency virus (HIV) on the soroconcordants heterosexual couples trajectory, identifying changes in the couples affective-sexual life and how they deal and face the diagnostic. It was developed at the Centro de Controle de Deficiências Imunológicas (CCDI) at Universidade Federal de São Paulo (UNIFESP) and two couples in which both the partners had positive sorology to HIV in assintomatic fase took part. Two interviews have been done with each couple, starting by a semi-structuralized script, wich was also a familiar genogram. By analysing the context the informations have been discussed under the light of General Systems Theory and Attachment Theory. In participants narratives it was possible to identify familiars patterns s influences in the formation of the couple, the development of its conjugality facing the diagnostic of positive sorology to HIV. Masculine unfaifthfulness, the way in to the infection on both studied couples, was responsible for feelings suchs as anger, fear, desperation and guilt. Quotidian living directs new ways for sexual life including abstinence, health care and taking medicines, adaptations relative to secundary losses as job and keeping secrets